Megaprojects paradox and Ecuadorian road budget management 2002-2006 - Moreno Parra, Iván Manuel (2023)
Based on cost overruns of 80 % in the Chanel Tunnelbetween the United Kingdom and France, 220 % in the Big Dig in Boston, 1400 % in the Sydney Opera House and similar cases around the world, unlike the previous ones, this research analyzes how its scope affects a set of infrastructure projects instead of isolating each one to study it, answering the following question: Between 2002 and 2006, did an annual perspective budget regulation affect Ecuadorian road projects? Thus, cost overruns, delays in construction schedule and shortfall in estimated benefits were identified (in addition to those of previous studies) derived from budget management that did not establish the limit of resources available in the medium term, allowing politicians to seize resources required by road projects in execution to finance new ones.